1997
DOI: 10.1128/iai.65.8.3286-3292.1997
|View full text |Cite
|
Sign up to set email alerts
|

Complement fragment C5a and inflammatory cytokines in neutrophil recruitment during intramammary infection with Escherichia coli

Abstract: Generation of inflammatory mediators and leukocyte recruitment to infection at an epithelial surface were studied during Escherichia coli-induced mastitis. One uninfected gland of each of eight midlactation cows was challenged with only 30 CFU of E. coli McDonald strain 487, a serum-resistant isolate from a cow with mastitis. Bacteria grew logarithmically during the first 10 to 12 h after challenge, reaching concentrations of more than 10 5 CFU/ml with no detectable host response during this time. An intense i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(86 citation statements)
references
References 40 publications
5
76
0
5
Order By: Relevance
“…2000), whereas Shuster et al. observed cytokine and complement secretion following an Escherichia coli ‐induced mastitis (Shuster et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000), whereas Shuster et al. observed cytokine and complement secretion following an Escherichia coli ‐induced mastitis (Shuster et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of IL‐8 concentrations in cell culture supernatants with and without PMN, a commercial ELISA‐kit (Quantikine ® , IL‐8 ELISA; R&D Systems, Wiesbaden, Germany) approved in detecting bovine IL‐8 (Shuster et al. 1997; Boudjellab et al.…”
Section: Methodsmentioning
confidence: 99%
“…Although S. aureus and coliform mastitis are associated with high influx of neutrophils, their activation state and CD markers expression are different. Shuster et al (1997) showed that recruited neutrophils expressed strong chemotactic activity with the ability to upregulate CD18. Whereas, neutrophils form quarters chronically infected with S. aureus were less active and with low tendency to express CD18 and CD11b (Riollet et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Milk IL-8 levels were determined from undiluted whey samples assayed with a commercially available human IL-8 ELISA kit (R&D Systems, Inc., Minneapolis, MN). The antibody pairs used in this kit have been previously shown to cross-react with bovine IL-8 (Shuster et al, 1996(Shuster et al, , 1997. The optical density at 450 nm and a correction wavelength of 550 nm were measured on a microplate reader.…”
Section: Elisa For Il-8mentioning
confidence: 99%